PET clinical study of novel antipsychotic LB-102 demonstrates unexpectedly prolonged dopamine receptor target engagement - Wong, Dean F.; Chand, Ganesh B.; Caito, Nicole; Eramo, Anna; Grattan, Vincent T.; Hixon, Mark S.; Nicol, Ginger; Lessie, Erin; Prensky, Zachary; Kuwabara, Hiroto; Tian, Lucy; Valenta, Ines; et al. (Neuropsychopharmacology, 2025)
Regulation of dopamine activity has important clinical consequences, most notably in schizophrenia. LB-102, N-methyl amisulpride, is a novel dopamine D2/3/5-HT7 inhibitor being developed as a treatment for schizophrenia and other psychiatric disorders. The characteristic that is common to all current antipsychotics is their engagement of D2 dopamine receptors. The goal of this study was to measure the dopamine receptor occupancy of orally administered LB-102 at three different doses (50, 75, and 100 mg as single doses and 50 and 100 mg as multiple doses) and at different timepoints in healthy volunteers using positron emission tomography (PET) with 11C raclopride as a radiotracer. Results of this study (NCT04588129) showed that steady-state once daily oral dosing of 50 mg LB-102 afforded striatal dopamine occupancy (RO) in the desired 60-80% range consistently over the course of 24 h. Contrary to the often observed relationship between RO vs plasma concentrations, maximum dopamine RO significantly lagged maximum plasma concentration and showed little variability under steady state conditions. A similar phenomenon has recently been reported with a non-racemic version of amisulpride [1]. LB-102 was generally safe and well-tolerated at all doses. Results of this study were used to inform dosing in a subsequent Phase 2 clinical study in schizophrenia patients.
Online verfügbar: 16 October 2024
Gesehen am 04.04.2025